Military Orthopedic Surgeons Are Not Just Traumatologists - Choufani, Camille; Barbier, Olivier; Mathieu, Laurent; de L'Escalopier, Nicolas (Military medicine, 2022)
Each French military orthopedic surgeon is both an orthopedic surgeon and a trauma surgeon. Their mission is to support the armed forces in France and on deployment. The aim of this study was to describe the type of orthopedic surgery performed for the armed forces in France. Our hypothesis was that scheduled surgery was more common than trauma surgery. We conducted a retrospective descriptive analysis of the surgical activity for military patients in the orthopedic surgery departments of the four French military platform hospitals. All surgical procedures performed during 2020 were collected. We divided the procedures into the following categories: heavy and light trauma, posttraumatic reconstruction surgery, sports surgery, degenerative surgery, and specialized surgery. Our primary endpoint was the number of procedures performed per category. A total of 827 individuals underwent surgery, 91 of whom (11%) were medical returnees from deployment. The surgeries performed for the remaining 736 soldiers present in metropolitan France (89%) consisted of 181 (24.6%) trauma procedures (of which 86.7% were light trauma) and 555 (75.4%) scheduled surgery procedures (of which 60.8% were sports surgery). Among the medical returnees, there were 71 traumatology procedures (78%, of which 87.3% were light traumatology) and 20 procedures corresponding to surgery usually carried out on a scheduled basis (22%, of which 95% were sports surgery). Military orthopedic surgeons are not just traumatologists; their activity for the armed forces is varied and mainly consists of so-called programmed interventions.